Dialogical inquiry: multivocality and the interpretation of text. (August 2021) - Wells, Ruth; Barker, Seamus; Boydell, Katherine; Buus, Niels; Rhodes, Paul; River, Jo
The aim of this paper is to describe a novel form of qualitative inquiry, dialogical inquiry, which allows for multiple investigators from different positions or traditions to collaboratively interpret qualitative data, engaging in a process of mutual influence to enrich both themselves and the process of analysis. We provide a clearly operationalized method, which is inspired by the philosophy of Bakhtin, as reimagined through practices from Open Dialogue, a social network–based approach to dialogical psychotherapy. Drawing on a specific text analysis of Jay Neugeboren's novel "Imagining Robert, " we demonstrate how our dialogical inquiry approach can bring reflexive practice in qualitative research to life through mutual reflections among investigators. We show how dialogical inquiry can generate appreciation for multiple perspectives, awareness of affective and epistemic positions, and new knowledge production. This approach could be particularly suited for research teams that wish to actively generate new kinds of knowledge, or to privilege the voices of coresearchers from diverse social, political, and epistemic positions.